2015
DOI: 10.1007/s11419-015-0294-5
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous humor analysis for the detection of xenobiotics in forensic toxicology: a review

Abstract: Vitreous humor (VH) is a gelatinous substance contained in the posterior chamber of the eye, playing a mechanical role in the eyeball. It has been the subject of numerous studies in various forensic applications, primarily for the assessment of postmortem interval and for postmortem chemical analysis. Since most of the xenobiotics present in the bloodstream are detected in VH after crossing the selective blood-retinal barrier, VH is an alternative matrix useful for forensic toxicology. VH analysis offers parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 273 publications
2
65
0
7
Order By: Relevance
“…These results in vitreous when compared to femoral blood are in agreement with a previous study (R 2 = 0.26; n = 40, 61 as are the results of femoral blood to cardiac blood (R 2 = 0.76) and psoas muscle (R 2 = 0.75) 16 but do not agree with the results of two other studies that showed significant correlations between femoral blood and vitreous concentrations (R 2 = 0.87; p < 0.01, n = 69 62 ), (R 2 = 0.72; p < 0.001, n = 52 60 ), and (R 2 = 0.79; p > 0.001, n = 45 16 ). The differing sets of results obtained by the various groups and this study show that although correlations may exist for populations due to differences such as individual tolerance, individual metabolism, survival time after the administration of the drug, and also postmortem redistribution, 63,64 in the absence of a femoral blood sample in a case other samples should not be used to attempt to determine the femoral blood concentration.…”
Section: Relationships Between and Femoral Blood And The Other Varimentioning
confidence: 71%
“…These results in vitreous when compared to femoral blood are in agreement with a previous study (R 2 = 0.26; n = 40, 61 as are the results of femoral blood to cardiac blood (R 2 = 0.76) and psoas muscle (R 2 = 0.75) 16 but do not agree with the results of two other studies that showed significant correlations between femoral blood and vitreous concentrations (R 2 = 0.87; p < 0.01, n = 69 62 ), (R 2 = 0.72; p < 0.001, n = 52 60 ), and (R 2 = 0.79; p > 0.001, n = 45 16 ). The differing sets of results obtained by the various groups and this study show that although correlations may exist for populations due to differences such as individual tolerance, individual metabolism, survival time after the administration of the drug, and also postmortem redistribution, 63,64 in the absence of a femoral blood sample in a case other samples should not be used to attempt to determine the femoral blood concentration.…”
Section: Relationships Between and Femoral Blood And The Other Varimentioning
confidence: 71%
“…The main drawback of this specimen is the low volume that can be collected during a forensic autopsy (at best about 5 ml). A large number of compounds can be detected in this specimen, being of great interest in forensic toxicology, as has been demonstrated by many authors [63]. Actually, this specimen can be useful in forensic toxicology for SA analysis as a complementary sample to blood and/or urine when considering intake of SD, even though the studies of SA disposition regarding vitreous humor are limited to a publication [24].…”
Section: Vitreous Humormentioning
confidence: 83%
“…Nevertheless, in forensic toxicology a diversity of biological matrices are used in addition to blood and urine. A large number of studies have been published describing the relevance of the developed methodologies for the analysis of drugs of abuse in various biological specimens, highlighting some review articles [60][61][62][63]. In this review, on the basis of reports published between 2004 and 2015 describing the analysis of SA in human biological specimens, different analytical methodologies in conventional and unconventional matrices (blood, plasma, urine, vitreous humor, pericardial fluid, sweat, oral fluid and hair), with special attention to its advantages and disadvantages, are introduced [15,[24][25][26][54][55][56].…”
Section: Toxicological Analysis In Biological Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional methods for determining the composition of fats are gas and liquid chromatography [21][22][23][24][25]. However, it is clear that new alternative analytical procedures for the analysis of the adipose are very much desired [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%